ANALISIS PERLAKUAN AKUNTANSI TERHADAP PELEPASAN DAN PENGHENTIAN ASET TETAP PADA PT. X - Toisuta, Elshinta; Kalangi, Lintje; Pangerapan, Sonny (Universitas Sam Ratulangi, 2019)
The disposal and termination of fixed assets in an entity can be carried out in various ways, like disposing, selling, and exchanging. The fixed assets are released and discontinued because of damage or fixed assets have been expired so that they no longer provide economic benefits to the company. The accounting treatment for the disposal and termination of fixed assets is seen in terms of recognition, measurement and presentation. This study aims to determine whetherÂ the accounting treatment of the disposal and termination of fixed assets is in accordance with PSAK No. 16. The research method used is descriptive method. The collected data and information are in accordance with the facts and actual condition that occur within company. The results show that the accounting treatment of the disposal and termination of fixed assets in terms of recognition and presentation is in accordance with PSAK No. 16. While in terms of measurement, it is still not in accordance with PSAK No. 16.